Respuesta :
Answer:
[tex]=-2nm^2+2nm+6n[/tex]
Step-by-step explanation:
[tex]-2n\left(m^2-m-3\right)\\\mathrm{Distribute\:parentheses}\\=\left(-2n\right)m^2+\left(-2n\right)\left(-m\right)+\left(-2n\right)\left(-3\right)\\Apply\:minus-plus\:rules\\+\left(-a\right)=-a,\:\:\left(-a\right)\left(-b\right)=ab\\=-2nm^2+2nm+2\cdot \:3n\\\mathrm{Multiply\:the\:numbers:}\:2\cdot \:3=6\\=-2nm^2+2nm+6n\\[/tex]
Answer: [tex]-2nm^{2} +2nm+6n[/tex]
Step-by-step explanation:
Expand by distributing terms.
[tex]-(2nm^{2} -2nm-6n)[/tex]
Remove parentheses.
[tex]-2nm^{2} +2nm+6n[/tex]